PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BANK PERKREDITAN RAKYAT (BPR) BATURAJA - Rani Anwar (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2019)
The purpose of this study was to determine the influence of work environment and work motivation on employees performance in PT. Bank Perkreditan Rakyat (BPR) Baturaja affect either partially or simultaneously. This research used data from primary data collected directly from the object under study using questionnaries. The analysis used is multiple linear regression analysis, t test, F test, and coefficient of determination. The result of this study found that partially the work environment variables affect the performance of employees of PT. Bank Perkreditan Rakyat (BPR) Baturaja with t count 12.475 > 2.3483 (Ha accepted and Ho rejected) while work motivation does not affect the performance of the employees of PT. Bank Perkreditan Rakyat (BPR) Baturaja because t count -0.357 > 2.3483 (Ha is rejected and Ho is accepted. While simultaneously the variables X1 and variables X2 affect the variable Y with F count 319.868 > 3.28. The result of this research is expected to be used as a suggestion for company should further improve the working environment and working motivation so that employees performance can be increased.